G. Hasen Jaeger, Introduction to the basic Concepts and Problems of Modern Logic, D. Reidel Publishing Company, Dordrecht-Holland, 1972, 180 pp - Alegría de Bun, Afra (1973)
Fil: Alegría de Bun, Afra. Pontificia Universidad Católica Argentina; Argentina